The Role of Human Capital in Economic Growth : The Case of Spain - Mauro, Paolo (IMF Working Papers; Working Paper ;, 2000)
This study constructs an index of human capital for the Spanish labor force over the past two decades and projects it over the next decade on the basis of likely demographic developments. The methodology considers both educational attainment resulting from formal schooling and improvements in workers' productivity resulting from experience, or 'learning by doing.' Furthermore, it allows for the fact that people with higher education accumulate human capital through learning by doing at a faster pace than less educated workers or, in other words, that the full returns to formal schooling are realized with a lag of many years. Using this index, a growth accounting exercise is conducted to estimate the impact of human capital accumulation on economic growth over the past two decades. Finally, potential output growth is projected over the next few years, taking into account the impact of human capital accumulation.